2016
DOI: 10.4103/2279-042x.185750
|View full text |Cite
|
Sign up to set email alerts
|

A study of medication-related problems in stroke patients: A need for pharmaceutical care

Abstract: Objective:The study was aimed to assess the incidence and characteristics of drug-related problems (DRPs).Methods:A prospective, observational study was conducted among 133 patients with stroke disease who were aged 18 years or older and admitted to the general medicine ward. During the 6 months study period, the incidence of DRPs was identified using the Pharmaceutical Care Network Europe Foundation classification system, version 6.2.Findings:A total of 133 patients were screened for DRPs. Among them, 120 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Previous studies investigating the role of pharmacists in various hospital departments and adult and pediatric patients have shown that their care can decrease the rate of drug-related problems and improve patient outcomes. [25,26] However, other studies have found that while the incidence of drug-drug interactions or DRPs may decrease there was no obvious difference in clinical outcomes. [27,28] Optimizing pharmacotherapy in the form of drug selection and avoiding major drug-drug interactions may inhibit disease complications and shorten hospital stays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigating the role of pharmacists in various hospital departments and adult and pediatric patients have shown that their care can decrease the rate of drug-related problems and improve patient outcomes. [25,26] However, other studies have found that while the incidence of drug-drug interactions or DRPs may decrease there was no obvious difference in clinical outcomes. [27,28] Optimizing pharmacotherapy in the form of drug selection and avoiding major drug-drug interactions may inhibit disease complications and shorten hospital stays.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies to date have focused on the roles of pharmacists, such as the identification and classification of DRPs, [6,25,26] with intervention happening on the recommendations and acceptance of doctors. More direct measurement of the influence of clinical pharmacists is based on observations of the patient’s clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Northern Sweden looking into the occurrence and character of TRPs among old patients with dementia or cognitive impairment, found that ineffective drug/inappropriate drug (efficacy problem category) and unnecessary drug therapy were the most common TRPs among patients with an earlier stroke (Pfister et al, 2017). In India, 120/133 patients with stroke were found to have at least one TRPs, and drug efficacy problem was found to be the highest among the TRPs identified, accounting for 35.0% (Kanagala et al, 2016). In a study conducted in Germany, TRPs occurred in 105/155 (67.7%) patients with transient ischemic attack or ischemic stroke, giving a mean of 1.80 ± 2.00 TRPs per patient; inappropriate “drug” therapy, “indication”, and “dosage” were the most common TRPs identified (Hohmann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Europe revealed that the use of medication as a preventive measure for stroke patients is ineffective to a significant extent, with a rate of 32.28%. 18 The primary concern in tertiary prevention for stroke patients extends beyond the efficacy of medications, encompassing the issue of patient adherence to medication, which hinders the attainment of ideal tertiary preventive outcomes. A multicenter study conducted in a hospital revealed that 70% of the patients who received pharmacological treatment exhibited an increase in severity following drug therapy.…”
Section: Methods Study Designmentioning
confidence: 99%